Erythrocyte Osmotic Fragility of Nera Black Fowls of Two - Age Groups - Azeez, O.I.; Oyewale, J.O.; Okunola, O.O. (International Journal of Poultry Science, 2009)
The erythrocyte osmotic fragility and other erythrocyte indices in fowls of two different age groups (7-9 week-old and 49 week-old) were studied using Nera Black strain usually raised commercially for egg production in Nigeria. Erythrocytes in the 49 week-old birds were more fragile than those in the 7-9 week-old at sodium chloride (NaCl) concentrations of 0.2% (p<0.05), 0.7% (p<0.05), 0.8% (p<0.01) and 0.9% (p<0.01). The mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCH) values were also higher in the adults, but the packed cell volume (PCV) was lower. The haemoglobin (Hb) concentration, red blood cell (RBC) count and mean corpuscular volume (MCV) were similar in the two age groups.